J. C. Penney : activist investors and the rise and fall of Ron Johnson - Robinson, David (London : SAGE Publications Ltd, 2017)
The case study is set in 2012 and 2013. J.C. Penney is a venerable American institution, one of the last surviving department store chains. But it has suffered from "profitless prosperity" good "top line" (revenue) but great difficulty in bringing much to the "bottom line" (net income). Additionally, competition from specialty retailers has led Penneys to abandon certain lines of business (such as automotive repair) and face intense competition in other categories (wear-to-work clothing and household goods). The case study discusses the hiring of Ron Johnson from Apple in 2011 and the aftermath of Johnsons new strategy of a curated collection of 100 brands and change in pricing strategy from frequent sales to everyday low pricing. The case study also shows the aftermath of Johnsons strategy which was not positive.
Originally published: Robinson, D. (2014). J. C. Penney: Activist investors and the rise and fall of Ron Johnson. The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Penney, J. C. -- 1875-1971.; J.C. Penney Co; Merchants -- United States -- Case studies; Retail trade -- United States -- Case studies; Stores, Retail -- United States -- Case studies